Acceptance Model Of Open Educational Resources Platform Among Saudi Teachers - Saud S, Alshammari, Waleed (2024)
The usage of open educational resources (oer) by saudi teachers is expected to enhance education outcomes, in line with the government's goal to promote technology in education. However, the using the oer ‘shms’ platform by school teachers is still limited and the reasons behind remain unclear due to limited research. To address the gap, this study used utaut to explore factors affecting teachers' use of the oer shms platform. Internal factors like performance expectancy, effort expectancy, anxiety, and self-efficacy, along with external factors like social influence and facilitating conditions, were suggested to impact saudi teachers' use of the platform through intention as a mediator. The study adopted a mixed-method research design in which quantitative and qualitative approaches. The instruments used for data collection were closed-ended questionnaires with 360 saudi school teachers. Additionally, semi-structured interviews were conducted with seven teachers to support survey findings. The data was analyzed using partial least square-structural equation modelling through smartpls version 3.3.3 software for quantitative data while thematic analysis was used for qualitative data. The findings revealed that performance expectancy, effort expectancy, social influence, anxiety, and self-efficacy significantly influence teachers’ intention to use of oer shms platform. Similarly, facilitating conditions and intention significantly influence teachers’ use of the oer shms platform.